A Regional and Social Dialectology of the BATH Vowel in South African English. (20th February 2015) - Mesthrie, Rajend; Chevalier, Alida; Dunne, Timothy
Abstract This paper provides the beginnings of a pan–South African English dialectology, characterizing five cities (Cape Town, Port Elizabeth, Kimberley, Johannesburg, and Durban) and four ethnicities (Black, Colored, Indian, and White), via a single vowel, BATH (or /ɑ:/). From interviews with 200 selected speakers, 5553 tokens were subjected to acoustic analysis via PRAAT (Boersma & Weenink, 2010), yielding bivariate data on vowel quality. Statistical analysis via analysis of variance focused on sets of five persons in each of 40 city-ethnicity-gender combinations. Overall, no city shows cohesion across all ethnic groups, though Kimberley, the smallest of the cities, and Johannesburg, the largest, come close. Conversely, no ethnicity shows cohesion across all cities, although Black speakers of traditional L2 English background come close. There is a robust regional difference for Colored speakers between Johannesburg and the other cities. Gender effects are notable: women's means are closer to the historically prestige [ɑ:] variant than the historically broader variant [ɔ:] in 6 of 20 possible groupings by city and ethnicity; in none of the cases is the opposite true.